Comprehensive analysis of the full-length transcripts and alternative splicing involved in clubroot resistance in Chinese cabbage - He-nan SU; Yu-xiang YUAN; Shuang-juan YANG; Xiao-chun WEI; Yan-yan ZHAO; Zhi-yong WANG; Liu-yue QIN; Zhi-yuan YANG; Liu-jing NIU; Lin LI; Xiao-wei ZHANG (Journal of Integrative Agriculture, 2023)
Chinese cabbage is an economically important Brassica vegetable worldwide, and clubroot, which is caused by the soil-borne protist plant pathogen Plasmodiophora brassicae is regarded as a destructive disease to Brassica crops. Previous studies on the gene transcripts related to Chinese cabbage resistance to clubroot mainly employed RNA-seq technology, although it cannot provide accurate transcript assembly and structural information. In this study, PacBio RS II SMRT sequencing was used to generate full-length transcriptomes of mixed roots at 0, 2, 5, 8, 13, and 22 days after P. brassicae infection in the clubroot-resistant line DH40R. Overall, 39 376 high-quality isoforms and 26 270 open reading frames (ORFs) were identified from the SMRT sequencing data. Additionally, 426 annotated long noncoding RNAs (lncRNAs), 56 transcription factor (TF) families, 1 883 genes with poly(A) sites and 1 691 alternative splicing (AS) events were identified. Furthermore, 1 201 of the genes had at least one AS event in DH40R. A comparison with RNA-seq data revealed six differentially expressed AS genes (one for disease resistance and five for defensive response) that are potentially involved in P. brassicae resistance. The results of this study provide valuable resources for basic research on clubroot resistance in Chinese cabbage.